(untitled) (Journal of Oriental Studies, 2023)
This paper aims to analyze South Korea’s science diplomacy engagement with Central Asia, particularly through official development assistance (ODA). It investigates how South Korea’s science and technology (S&T) ODA can align with its science diplomacy in the region, with a focus on the flagship project of establishing a Center of Chemical Technology in Uzbekistan (UzCCT). Through this project, South Korea aims to showcase its technological expertise and contribute to the economic growth of its partner countries. To achieve this, the paper provides a brief overview of previous research on science diplomacy and South Korea’s science diplomacy evolution, examining its characteristics and limitations. The paper then shifts to South Korea’s ODA in Central Asia, utilizing a case study approach to illustrate the effective use of science diplomacy and S&T ODA in supporting economic development and strengthening diplomatic ties. Key words: South Korea, Central Asia, Science Diplomacy, Science and Technology ODA